As experiências sociais de idosos que fazem uso de álcool e outras drogas em municípios de fronteira - Fonseca Junior, Roberto da Cruz (2017)
This dissertation brings to the scene the social experiences of elderly people who use alcohol and other drugs and are in attendance at Centros de Atendimento Psicossocial álcool e outras drogas – CAPSad, located in municipalities on the border of Rio Grande do Sul. Drugs addiction is today a disease that affects the whole world, becoming one of the biggest public health problems that result in incapacity for labor, as well as it generates processes of violence, leading to even deaths. Older people are among the population segments affected by this problem and suffer from invisibility on the part of the State and stigmatization of society and family due to their state of illness. Therefore, professionals who work in the health area and daily care for elderly people need to be attentive to the problems that surround these users. This study seeks to analyze the social experiences of the elderly people who attend the CAPSad service, with their relatives, friends, work relations and with the service itself. We seek to problematize the processes that permeate the institutional reality, as well as the main characteristics of the sample of the elderly users of alcohol and other drugs served by the municipal mental health policy in the period of 2016. We interviewed eight elderly male users between the two CAPSad, One located in São Borja and another in Santana do Livramento on the border of Rio Grande do Sul and two key informants who work in these institutional spaces and who are part of the team. The research is based on the Materialistic, Historical and Dialectical Method, with a qualitative, exploratory and descriptive configuration, following the technique of content analysis according to Gil (1987). The results reveal that the social experiences of the elderly are diverse, but they are crossed by a patriarchal, violent, impoverished culture, in which the relationship of alcohol and other drugs with their social, family and community relations can be punctuated. Drug use began in general in childhood and adolescence, and is not an expression of the aging process. The use of alcohol as an expression of the social question is evidenced when analyzing the social experiences of the elderly, whose alcohol consumption becomes exacerbated due to relationships with work, unemployment and the process of structural violence that surrounds their daily life. The low demand of elderly women for CAPSad care is evident, which also impacts on the invisibility of gender issues in the care provided in CAPSad. This is due to the patriarchal culture and traditional gender roles that contribute to a greater stigmatization of women who use alcohol and drugs, regardless of age. It is concluded that there is a need for a greater capacity of professionals to meet the specificities of gender, generation and other identity markers that permeate the social experiences of the subjects, and greater investments of the State in CAPSad for playing a fundamental role for the treatment of users ( As well as alcohol and other drugs, contributing to the improvement of the quality of life, with a view to social inclusion and the breakdown of stigmas associated with alcohol use, such as "vagabond", "shameless" or simply " Rubber "(drunk).